A Study on William Wordsworth As a Nature Poet: Exploring Wordsworth's Unique Perspective on Nature (Journal of Advances and Scholarly Researches in Allied Education, 2014)
As a poet of Nature,Wordsworth stands supreme. He is a worshipper of Nature, Nature’s devotee orhigh-priest. His love of Nature was probably truer and tenderer, than that ofany other English poet, before or since. Nature comes to occupy in his poem aseparate or independent status and is not treated in a casual or passing manneras by poets before him. Wordsworth had a full-fledged philosophy, a new andoriginal view of Nature. Three points in his creed of Nature may be noted: